Epiregulin enhances tumorigenicity by activating the ERK/MAPK pathway in glioblastoma. (26th January 2014) - Kohsaka, Shinji; Hinohara, Kunihiko; Wang, Lei; Nishimura, Tatsunori; Urushido, Masana; Yachi, Kazuhiro; Tsuda, Masumi; Tanino, Mishie; Kimura, Taichi; Nishihara, Hiroshi; Gotoh, Noriko; Tanaka, Shinya
Abstract: Background: Glioblastoma multiforme (GBM) is one of the most aggressive human tumors, and the establishment of an effective therapeutic reagent is a pressing priority. Recently, it has been shown that the tumor tissue consists of heterogeneous components and that a highly aggressive population should be the therapeutic target. Methods: Through a single subcutaneous passage of GBM cell lines LN443 and U373 in mice, we have developed highly aggressive variants of these cells named LN443X, U373X1, and U373X2, which showed increased tumor growth, colony-forming potential, sphere-forming potential, and invasion ability. We further investigated using microarray analysis comparing malignant cells with their parental cells and mRNA expression analysis in grades II to IV glioma samples. Results: Adipocyte enhancer binding protein 1, epiregulin (EREG), and microfibrillar associated protein 5 were identified as candidate genes associated with higher tumor grade and poor prognosis. Immunohistochemical analysis also indicated a correlation of a strong expression of EREG with short overall survival. Furthermore, both EREG stimulation and EREG introduction of GBM cell lines were found to increase phosphorylation of epidermal growth factor receptor (EGFR) and extracellular signal-regulated kinase and resulted in the promotion of colony formation, sphere formation, and in vivo tumor formation. Gefitinib treatment inhibited phosphorylation of EGFR and extracellular signal-regulated kinase and led to tumor regression in U373-overexpressed EREG. Conclusion: These results suggested that EREG is one of the molecules involved in glioma malignancy, and EGFR inhibitors may be a candidate therapeutic agent for EREG-overexpressing GBM patients.